FAKTOR – FAKTOR YANG MEMPENGARUHI PERILAKU PERSONAL HYGIENE SAAT MENSTRUASI PADA REMAJA PUTRI: LITERATURE REVIEW - Hamidah, Esthi Nur; Realita, Friska; Kusumaningsih, Meilia Rahmawati (Coping: Community of Publishing in Nursing; Vol 10 No 3 (2022): Juni 2022, 2022)
Personal hygiene during menstruation is important and needs to be considered to prevent bacteria, viruses, and other microorganisms. personal hygiene during menstruation can lead to diseases of the reproductive organs, such as Reproductive Tract Infections. The aim of this literature review was determined the factors that influence personal hygiene during menstruation in adolescent girls. This study uses the literature review method, where articles are searched through Google Scholar and PubMed using keywords such as menstrual hygiene, adolescent, factors, and practices. Selected articles based on 2016 – 2021, full text, English and Indonesian articles. Based on the 10 articles that have been described, the factors that influence the personal hygiene behavior of adolescents during menstruation are parental education, especially mothers, family socio-economics, adolescent knowledge, adolescent age, availability of facilities, and myths about menstruation. There is an influence of parental education, family socio-economic, adolescent knowledge, adolescent age, availability of facilities, and myths on personal hygiene during menstruation.